2014
DOI: 10.1097/coc.0b013e31826e0703
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Pilot Study of Target-guided Personalized Chemotherapy with Intensity-modulated Radiotherapy in Patients With Early Rectal Cancer

Abstract: The individualization of neoadjuvant chemotherapy in patients with rectal cancer is feasible and leads to a high rate of pathologic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Studies on gastrointestinal cancers have suggested that overexpression of TOP1 predicts benefit of camptothecin-based therapies [8488]. However, the evidence associated with the predictive effect of TOP1 expression status and therapy outcome was mostly of low-level and studies often reported inconclusive results [89–91] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on gastrointestinal cancers have suggested that overexpression of TOP1 predicts benefit of camptothecin-based therapies [8488]. However, the evidence associated with the predictive effect of TOP1 expression status and therapy outcome was mostly of low-level and studies often reported inconclusive results [89–91] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a pilot study of RT with personalized chemotherapy and biological therapy based on molecular markers (TOPO-1, ERCC1 expression, KRAS, BRAF, and PI3K) used capecitabine and either irinotecan (if TOPO-1 high) or oxaliplatin (if ERCC1 low), and either VEGF-or EGFR-targeted agents (if KRAS wildtype) among 16 patients with T3 or N1 rectal cancers [68]. The ypCR rate was promising at 50 %, which offers a potential basis for future molecularly driven larger studies.…”
Section: Anti-epidermal Growth Factor Therapymentioning
confidence: 99%
“…There is currently no role for the addition of EGFR‐targeted therapy as a radiosensitizer in the treatment of LARC. However, a pilot study of RT with personalized chemotherapy and biological therapy, based on molecular markers among 16 patients with T3 or N1 rectal cancers, showed a pCR rate of 50 per cent, which may be the basis for future molecular guided studies.…”
Section: Epidermal Growth Factor Receptor Inhibitorsmentioning
confidence: 99%